2012
DOI: 10.1364/oe.20.013824
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly-enhanced harmonic generation in Argon

Abstract: We present systematic investigations of harmonic generation in Argon, driven in the vicinity of a five-photon resonance by intense, tunable picosecond radiation pulses. When properly matching the laser frequency with the Stark-shifted multi-photon resonance, we observe a pronounced enhancement not only of the 5th, but also the 7th and 9th harmonic of the driving laser (i.e. at orders higher than the involved multi-photon resonance). We study the harmonic yield at different intensities and wavelengths of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…We do this by first solving the time-dependent Schrödinger equation (TDSE) in the single active electron (SAE) approximation for wavelengths between 425 − 500 nm and for intensities up to 140 TW/cm 2 . We have chosen the intensity and wavelength regime such that the Keldysh parameter, of approximately 2, is in line with previous studies [11,15,21]. We identify resonant enhancement of harmonics 7, 9, and 11 (H7, H9, H11) due to Stark-shifted resonances between the ground state and the 1s2p, 1s3p, and 1s4p states.…”
Section: Introductionmentioning
confidence: 78%
“…We do this by first solving the time-dependent Schrödinger equation (TDSE) in the single active electron (SAE) approximation for wavelengths between 425 − 500 nm and for intensities up to 140 TW/cm 2 . We have chosen the intensity and wavelength regime such that the Keldysh parameter, of approximately 2, is in line with previous studies [11,15,21]. We identify resonant enhancement of harmonics 7, 9, and 11 (H7, H9, H11) due to Stark-shifted resonances between the ground state and the 1s2p, 1s3p, and 1s4p states.…”
Section: Introductionmentioning
confidence: 78%
“…Resonant HHG may increase the harmonic yield through a number of different mechanisms35363738394041. For H21 with photon energy of 25.2 eV, the closest resonance is the 3s 2 3p 6  → 3s 1 3p 6 4p 1 transition (26.6 eV), which is a window resonance4243.…”
Section: Resonant Hhgmentioning
confidence: 99%
“…These studies comprise both the theoretical treatment and the first attempts to achieve the resonance conditions in gas HHG experiments. While theoretical estimates testify the possibility of efficient enhancement of individual harmonics and groups of harmonics, experiments in gases revealed the difficulties encountered in the observation of resonantly enhanced single harmonic [20]. Further developments have revealed that the use of laser ablation plasma media could largely facilitate the resonance enhancement of harmonics.…”
Section: Introductionmentioning
confidence: 99%